KESETARAAN KEDUDUKAN ANAK LAKI-LAKI DAN PEREMPUAN DALAM TINDAK PIDANA PENCABULAN - Adi Wijaya; Muhamad Japri; Aji Titin Roswitha (The Juris, 2025)
Article 82(1) of Law No. 35 of 2014 on Child Protection stipulates that “any person” who commits or allows an act of indecency against a child shall be subject to criminal sanctions. However, law enforcement practices show a consistent pattern in which only male minors are prosecuted, while female minors who similarly commit or permit such acts are not treated as criminal subjects. This disparity raises concerns regarding the principle of equality before the law and the proper interpretation of the term “any person” within the provision. This study aims to analyze the legal standing of male and female minors as perpetrators in indecency cases and to examine whether female minors also meet the elements of criminal liability under Article 82. The findings indicate that both male and female minors who consciously engage in or allow indecent acts fulfill the objective and subjective elements of the offense and therefore hold equal legal status as potential perpetrators. Nevertheless, in practice, law enforcement still reflects gender bias by automatically positioning females as victims. The study recommends developing clearer procedural guidelines, enhancing gender sensitivity among investigators, and revising the statutory language to eliminate interpretive ambiguity.